Celebrating and advancing the scholarship of David P. Lepak (1971–2017): special issue introduction. Issue 2 (19th January 2021) - Takeuchi, Riki; Gong, Yaping; Boon, Corine; Jiang, Kaifeng
Abstract: This special issue is devoted to Professor David P. Lepak, who passed away on December 7, 2017. The special issue is meant to honor Professor Lepak's (or affectionately called Dave among his close friends and peers) intellectual contribution to the field of human resource management (HRM) and his academic influence on many of us who study HRM-related topics. We first introduce the special issue by highlighting three research topics that were central to Dave's work: (1) strategic management of human capital resources; (2) strategic HRM; and (3) multilevel HRM. We then introduce nine articles in the special issue and discuss how each of them contributes to one or more of the three topics of Dave's interest. We also provide a general discussion of all the articles and offer directions for future research.